Energy minimisers of perturbed dislocation energies. (June 2023) - Mateu, J.; Mora, M.G.; Rondi, L.; Scardia, L.; Verdera, J.
Abstract: In this paper we show that ellipses persist as energy minimisers under small perturbations, starting from a nonlocal energy inspired by edge dislocations. The case of Coulomb energies has been recently considered by the same authors.